Finding Love in The Pages of The Newspaper: An Analysis of The Kompas Contact Column in 1997 - Mokoginta, Fatimah; Rochwulaningsih, Yety; Puguh, Dhanang Respati (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2026)
The